2004
DOI: 10.1667/rr3196
|View full text |Cite
|
Sign up to set email alerts
|

A Sense of Danger from Radiation1

Abstract: Tissue damage caused by exposure to pathogens, chemicals and physical agents such as ionizing radiation triggers production of generic "danger" signals that mobilize the innate and acquired immune system to deal with the intrusion and effect tissue repair with the goal of maintaining the integrity of the tissue and the body. Ionizing radiation appears to do the same, but less is known about the role of "danger" signals in tissue responses to this agent. This review deals with the nature of putative "danger" si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
227
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(241 citation statements)
references
References 192 publications
6
227
0
2
Order By: Relevance
“…For example, RT alone was recently shown to be able to stimulate intratumoral lymphocytes responsive to both a foreign model Ag and an endogenous tumor Ag in an OVAexpressing B16 melanoma tumor model. 3 However, while RT seems able to generate 'danger' signals in general there is little to suggest that these are potent 9 for the development of specific adaptive immunity. Immune stimulation may be additionally required and a recent randomized phase II clinical trial study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, RT alone was recently shown to be able to stimulate intratumoral lymphocytes responsive to both a foreign model Ag and an endogenous tumor Ag in an OVAexpressing B16 melanoma tumor model. 3 However, while RT seems able to generate 'danger' signals in general there is little to suggest that these are potent 9 for the development of specific adaptive immunity. Immune stimulation may be additionally required and a recent randomized phase II clinical trial study.…”
Section: Discussionmentioning
confidence: 99%
“…3 The attraction of RT combined with IT is increased by findings that irradiation can modulate expression of several classes of genes in both murine and human cancers, 4 such as Fas, MHC-1, ICAM-1, and MUC-1, that might enhance their ability to serve as immune targets. 2,[5][6][7] On the other hand, while there is evidence that RT generates 'danger' signals that might mature dendritic cells (DCs) to present tumor antigen 8,9 there is no good evidence that this occurs in the clinic and such signals may be too weak to be effective. In a recent randomized phase II clinical trial study, 10 addition of recombinant vaccine administration to standard RT in patients with clinically localized prostate cancer showed that vaccination was safe and the generation of a PSAspecific cellular immune response was enhanced following RT.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocyte radiosensitivity is well established and remains the dominant explanation for this effect. However, substantial evidence suggests more varied effects of radiation on the immune system, prompting the re-characterization of radiation as 'immunomodulatory' rather than immunosuppressive (McBride et al, 2004). Increased expression of proinflammatory cytokines, including TNF-a and IL-1b following radiation has been reported (Hallahan et al, 1989;Ishihara et al, 1995;Nemoto et al, 1995;Hong et al, 1999).…”
Section: Revisiting the Role Of Radiationmentioning
confidence: 99%
“…Increased expression of proinflammatory cytokines, including TNF-a and IL-1b following radiation has been reported (Hallahan et al, 1989;Ishihara et al, 1995;Nemoto et al, 1995;Hong et al, 1999). These observations suggest a potential role for radiation in signaling 'danger' and, perhaps, in the activation of antigen presenting cells (McBride et al, 2004). Notwithstanding this, studies aimed at determining the effects of radiation on antigen-presenting cell phenotype, cytokine expression and function have been somewhat contradictory.…”
Section: Revisiting the Role Of Radiationmentioning
confidence: 99%
“…TLRs are in serving as detectors of infectious diseases and cancer by activating dendritic cells (DCs) and other antigen-presenting cells to secrete proinflammatory cytokines and promoting DCs maturation to induct adaptive immune responses (Wang et al, 2008;Kumar et al, 2009). Ionizing radiation triggers production of generic "danger" signals may also activate effectors of innate immunity through TLR dependent mechanisms, and evoke the immune response to cancer (McBride et al, 2004;Roses et al, 2008). More than ten members (TLR1-10) of the TLR family have been reported (Rock et al, 1998;Du X et al, 2000;ChuangandUlevitch,2001).…”
Section: Introductionmentioning
confidence: 99%